2019
DOI: 10.1080/00325481.2019.1671667
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal vaccination: a discussion with all adolescents, whether college-bound or not

Abstract: Introduction: Adolescents and young adults are the primary reservoirs and transmitters of meningococci. In the US, meningococcal serogroup B (MenB) disease predominates over A, C, W, and Y; ACIPrecommended MenACWY and MenB vaccines are available. We investigated invasive meningococcal disease (IMD) burden and vaccination among non-college adolescents. Methods: IMD incidence by college attendance status and vaccination rates were analyzed using publicly available surveillance data. Results: 64/158 IMD cases occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…While college students are known to be at increased risk for meningococcal disease, Alderfer et al [ 64 ] note that 18–24 year old noncollege individuals are also at risk for the disease. Alderfer et al [ 64 ] compared incidence of IMD occurring among 18- to 24-year-olds based on college attendance. The authors reported that 64 of 158 cases of IMD (40.5%) occurred in noncollege 18- to 24-year-olds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While college students are known to be at increased risk for meningococcal disease, Alderfer et al [ 64 ] note that 18–24 year old noncollege individuals are also at risk for the disease. Alderfer et al [ 64 ] compared incidence of IMD occurring among 18- to 24-year-olds based on college attendance. The authors reported that 64 of 158 cases of IMD (40.5%) occurred in noncollege 18- to 24-year-olds.…”
Section: Discussionmentioning
confidence: 99%
“…For MenB vaccination, 0% (none) of the reported cases among noncollege students had received MenB versus 0–7% in those attending college This analysis also, identified disparities in MenACWY vaccination coverage among cases of meningococcal disease in noncollege 18- to 24-year-olds versus those in college, with 90–100% of college cases reporting vaccination with MenACWY versus 38–57% of noncollege cases reporting vaccination with MenACWY. These results highlight that while non-college adolescents bear a significant portion of disease burden meningococcal vaccination is most often discussed for those who are college-bound [ 64 ]. Additionally, the most recent CDC meningococcal disease surveillance report (2019) continues to show similar disparities in meningococcal vaccination status in individuals aged 18–24 years attending college versus those not attending college.…”
Section: Discussionmentioning
confidence: 99%